If

f(x) = 3x + 1 and f^-1 = x-1/3 ,

then f^-1(7) =

a . 22

b . 2

c . -2

Skip to content# If f(x) = 3x + 1 and f^-1 = x-1/3 , then f^-1(7) = a . 22 b . 2 c . -2

Mathematics ##
Comments (2) on “If f(x) = 3x + 1 and f^-1 = x-1/3 , then f^-1(7) = a . 22 b . 2 c . -2”

### Leave a Reply Cancel reply

If

f(x) = 3x + 1 and f^-1 = x-1/3 ,

then f^-1(7) =

a . 22

b . 2

c . -2

[tex]f^{-1}(7)=\dfrac{7-1}{3}=\dfrac{6}{3}=2[/tex]

B

You can find it by plugging 7 in for x in the f^-1(x). so, 7-1/3

6/3

2